DESCRIPTION OF EFFECTIVENESS OF CILOSTAZOL AND ASPIRIN AS ADJUVANT OF DIABETIC FOOT WAGNER GRADE II AND III - Nurikhwan, Pandji Winata; Noor, Zairin; Al Audhah, Nelly (Fakultas Kedokteran Universitas Lambung Mangkurat, 2014)
Abstract: Inflammation in patients with diabetic foot will activate platelets and cause aggregation and lead to stasis of blood flow. This inflammation is caused by infection of the diabetic foot. Management of diabetic foot infections in patients is the use of antibiotics. However, the presence of vascularization disorders causing antibiotic delivery to the site of infection to be disrupted so that the process of eradication of infection would be inhibited. One of inflamation markers on patient with diabetic foot is increasing of ESRs.The general objective of this study was to determine the efficacy difference between cilostazol and aspirin as an adjuvant to accelerate tissue healing of diabetic foot care Wagner Grade II â III based on erythrocyte sedimentation rate. This study is a descriptive study using the double-blind and randomized pretest-posttest design. A total of 14 samples is obtained by consecutive sampling. The results showed that four patients given cilostazol showed a 35% reduction in ESR and ten patients were given aspirin showed a 35% reduction in ESR. It can be concluded giving cilostazol and aspirin as adjuvant diabetic foot Wagner II and III showed a decrease in ESR.Â Key words: erythrocyte sedimentation rate, diabetic foot, cilostazol, aspirin. ListenÂ